2006
DOI: 10.1021/ie0601899
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Lactose over Sponge Nickel CatalystsKinetics and Modeling

Abstract: Kinetics of lactose hydrogenation to lactitol, an alternative sweetener, over Mo-promoted sponge nickel slurry catalyst in aqueous solutions was studied. Hydrogenation experiments were carried out batchwise in a three-phase laboratory-scale reactor (300 mL, Parr Co.), operating at 20−70 bar and between 110 and 130 °C. The main hydrogenation product was lactitol, while small amounts of lactobionic acid, lactulose, lactulitol, sorbitol, and galactitol were detected as byproducts. The lactitol selectivity within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…The sugar solution was saturated with hydrogen and preheated in a separate vessel before it was fed into the reactor. High stirring rates (1800 rpm) were used to ensure the operation under kinetic regime since our previous experiments with varying stirring rates showed that a rate of 1800 rpm was enough to suppress external mass transfer limitations [3]. Samples were withdrawn and analysed with HPLC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sugar solution was saturated with hydrogen and preheated in a separate vessel before it was fed into the reactor. High stirring rates (1800 rpm) were used to ensure the operation under kinetic regime since our previous experiments with varying stirring rates showed that a rate of 1800 rpm was enough to suppress external mass transfer limitations [3]. Samples were withdrawn and analysed with HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…The selective catalytic hydrogenation of naturally appearing sugar molecules to their corresponding sugar alcohols is an environmentally friendly route to the production of alternative sweeteners: solid metal-based catalysts are used in an aqueous environment and the hydrogen addition is materialized through catalytic reactions, thus avoiding the use of stoichiometric reducing agents and the subsequent production of inorganic salts as waste material [1][2][3]. The current production technology of sugar alcohols is based on the use of batchwise operating slurry reactors: finely dispersed, supported or sponge metal catalyst (catalyst particles smaller than 0.1 mm) are immersed in a batch of aqueous sugar solution, to which hydrogen is continuously added.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated pressures and temperatures are needed to have a high enough reaction rate. On the other hand, too high a temperature impairs the selectivity of the desired product, as has been demonstrated by Kuusisto et al (2006). An overview of some feasible processes and catalysts is provided by Kinetic experiments were carried out isothermally in autoclave reactors of sizes 300 and 600 ml.…”
Section: Case C: From Sugars To Sugar Alcoholsmentioning
confidence: 99%
“…Moreover, synthesized polyols can play a key role in the production of biofuels from renewable sources [15]. The most important saccharide hydrogenation processes are glucose, xylose, maltose, and lactose hydrogenation to the corresponding alcohols [15][16][17][18][19]. The catalytic method of D-glucose hydrogenation to D-sorbitol is a complex process ( Figure 1) providing several reaction routes.…”
Section: Introductionmentioning
confidence: 99%